Debates of Muslim Culture and Pakistani Literature - Khan, Saif Ullah; Younas, Humaira (Al-Irfan, 2021)
Literature reflect any society and culture. Literature is pretty much important in evolution and livelihood of every nation. Literature represents mental, cultural and ideological attributes of a nation. We can say that Pakistani Literature, and Muslim culture is somehow Pakistan’s political, religious, social and cultural history. Holy Quran has presented evident, flexible and comprehensive theory about human life. In fact, spending life according to the teachings of Holy Quran is Muslim culture. Muslim culture also has been called as Prophetic civilization, revelational culture, heavenly civilization and ideological culture. Muslim culture is based upon its religious faiths and theories, but it has also adopted from culture of other civilizations and absorbed their influence too. This absorption has been stimulated by the non-biased point of view of Muslim culture, and that’s why Muslim culture has promoted every field of life. Pakistan came into existence for the sake of Islam so its greatest heritage is Muslim culture. Muslim culture should be distinguished from the heritage of Muslims. Roots of Muslim culture are deepened in literature, art, architecture, nutrition and nutritional values, costumes, jewelry, pottery and most importantly in the revolution of thoughts and way of thinking. So that it may bring joyfulness and satisfaction in the fields of world. If we consider Islam as the thorough code of life , if we consider it the axis point of inner and outer elements of Muslim culture , then their is no conclusion and solution of it other than molding our cultural reflections according to Islamic values.